1981
DOI: 10.1007/bf00239115
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of submandibular salivary glands in dogs to blood-borne horseradish peroxidase (HRP)

Abstract: Horseradish peroxidase (HRP) was administered to the submandibular glands of dogs by close-arterial bolus-type injections, and its localisation was examined histochemically by light and electron microscopy. The HRP became widespread in the interstices of the glands and reached many central acinar lumina via scattered localised parts of their "tight" junctional complexes. Reaction product was less often found in the lumina of demilunes, which suggested that the intercellular junctions there were less "leaky". H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…3). As in the previous study (Garrett et al 1981) intercellular staining was not always strong around the most positive lumina and conversely not all sites with moderately strong staining between cells showed very much activity in the lumina.…”
Section: Structural Assessments (A) Light Microscopysupporting
confidence: 72%
See 4 more Smart Citations
“…3). As in the previous study (Garrett et al 1981) intercellular staining was not always strong around the most positive lumina and conversely not all sites with moderately strong staining between cells showed very much activity in the lumina.…”
Section: Structural Assessments (A) Light Microscopysupporting
confidence: 72%
“…Similar studies are now being made with dogs and, using bolus-type close-arterial injections of HRP, we have shown that some of it can pass by the paracellular route to enter acinar lumina in 'resting' submandibular glands (Garrett, Klinger & Parsons, 1981).…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations